RESPONSIBILITY OF LAND DEED MAKING OFFICER FOR SALE AND PURCHASE DEED BASED ON POWER OF ATTORNEY TO SELL LAND THAT VIOLATES RULES (Sengketi District Court Decision Number 15/Pdt.G/2021/PN Snt) - Muhammad Abimukti Primanto (Jurnal Ilmiah Advokasi, 2024)
The Land Deed Making Office (PPAT) is a public official responsible for creating authentic land deeds. In carrying out their duties, they also assist in land registration activities and the transfer of land rights. One way to transfer land rights is by creating a power of attorney to sell land based on Article 1792 of the Civil Code. The research method used is a doctrinal research type, which is descriptive and analyzed qualitatively. In the case of the district court ruling Sengeti Number 15/Pdt.G/2021/PN Snt, there was bad faith on the part of the buyer in fulfilling the power of attorney to sell in that case. This issue prompts the author to delve deeper into and reveal the accountability of the PPAT who created the power of attorney to sell, considering the bad faith motive of the buyer and the sanctions that can be imposed based on the legal events in this case.Keywords: Civil Code; The Land Deed Making Office; Power of Attorney to Sell